Partnership approach to tech: an industry vertical solution - Faust, Bill; Bailey, Mark (Henry Stewart Talks, 2021)
This case study shows an industry vertical solution, where developing and implementing holistic digital tools to streamline and automate processes yielded favourable (and even unexpected) results.